Consolidation and future upgrades to the CLEAR user facility at CERN - Dyks, LA; Burrows, P; Korysko, P; Et al. (JACoW Publishing, Geneva, Switzerland, 2021)
The CERN Linear Electron Accelerator for Research (CLEAR) at CERN has been operating since 2017 as a dedicated user facility providing beams for a varied range of experiments. CLEAR consists of a 20 m long linear accelerator (linac), able to produce beams from a Cs₂Te photocathode and accelerate them to energies of between 60 MeV and 220 MeV. Following the linac, an experimental beamline is located, in which irradiation tests, wakefield and impedances tudies, plasma lens experiments, beam diagnostics development, and terahertz (THz) emission studies, are performed. In this paper, we present recent upgrades to the entire beamline, as well as the design of future upgrades, such as a dogleg section connecting to an additional proposed experimental beamline. The gain in performance due to these upgrades is presented with a full range of available beam properties documented.